Peran Bank Tanah dalam Penanganan dan Pengembangan Tanah Terlantar - Winanda, Fadila Anggi; Yamin, Muhammad; Zaidar, Zaidar; Kaban, Maria (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research explores the role of Land Banks in handling and developing abandoned land in Indonesia. Through a qualitative approach using interviews and secondary data analysis, this research identified several key findings related to inventory, procurement, distribution and utilization of abandoned land. The research results show that although the Land Bank has made great efforts to manage abandoned land more efficiently and effectively, there are still a number of challenges that need to be overcome, such as a lack of accurate data, resistance from land owners, and lack of access to resources and technology. To overcome these challenges, the research recommends improving inter-agency coordination, participatory approaches in land acquisition, development of comprehensive mentoring programs, ongoing education and training for communities, as well as policy support that supports access to microcredit and marketing facilities. By implementing these recommendations, it is hoped that the Land Bank can function more effectively in supporting sustainable development and improving the welfare of society in Indonesia..